Effects, in vase, of soil type, humidity and fertilization on herbaceous cotton plants - Lima, Maria Lindomar de; Bezerra, José Ernesto Souto; Carvalho, Hugo O. (Pesquisa Agropecuaria Brasileira, 2014)
The main objective of this work was to evaluate the effects, in vase, of soil type, humidity and fertilization on the development of cotton plants (Gossypium hirsutum, L.) under greenhouse conditions. The trial was conducted at the "Centro Nacional de Pesquisa do Algodão" (CNPA) of the "Empresa Brasileira de Pesquisa Agropecuária" (EMBRAPA), located at Campina Grande, Paraíba, Brazil. The experiment was planned in a factorial 2 x 3 x 4 completely random design with three replications, where the effect of the variables soil, humidity and fertilization on the germination, plant height and cotton production were studied. The soils studied were a "Noncalcic Brown soil" and a "Red-Yellow Podzolic soil", both having quite different characteristics. The water levels used were 40, 60 and 80% of the porous space full of water. Four levels of fertilization were tested: (control, 150 ppm of N, 150 ppm of P, and 150 ppm of N + 150 ppm of P). The cotton cultivar used was SU-0450/8909. The soil variable affected only the plant height. Germination, plant height and production increased when the soil water content was incremented from 40 to 60%. Higher levels of water did not have much response. Fertilization harmed germination; however, on plant height and production it was highly beneficial, mainly with the NP treatment. The response of cotton to P application was greater than the response to N application.